A group-delivered self-management program reduces spasticity in people with multiple sclerosis: A randomized, controlled pilot trial. Issue 1 (March 2017) - Hugos, Cinda L; Bourdette, Dennis; Chen, Yiyi; Chen, Zunqiu; Cameron, Michelle
Background: Spasticity affects more than 80% of people with multiple sclerosis (MS), affecting activity, participation, and quality of life. Based on an international guideline, an MS spasticity group education and stretching program, MS Spasticity: Take Control (STC), has been developed. Objective: The objective of this paper is to determine whether STC with home stretching is associated with greater changes in spasticity than usual care (UC), consisting of an illustrated stretching booklet and home stretching but without group instruction or support, in people with MS. Methods: Ambulatory MS patients with self-reported spasticity interfering with daily activities were randomized to STC or UC. Individuals completed questionnaires regarding MS, spasticity, walking, fatigue and mood, and physical measures of spasticity and walking. Results: Thirty-eight of 40 participants completed both assessments. Mean total score and scores on two subscales of the MS Spasticity Scale-88 improved more with STC than with UC ( p < 0.03). There was no significant change in the Modified Ashworth Scale in either group. Mean scores on the Modified Fatigue Impact Scale, the Beck Depression Inventory-II, and the physical component of the Multiple Sclerosis Impact Scale-29 showed statistically and clinically significant improvements in the STC group only. Conclusions: Participation in STC improved self-reported impact of spasticity more than UC and provided encouraging improvements in other measures.